Performance Appraisal Management In Aviation Industry - ., Ratnamani (International Journal of Scientific Research and Management (IJSRM), 2015)
Now day’s aviation industry plays a vital role in global economy. It’s a key factor between air and land based transportation of goods and passengers. It is a part of international supply chain networks. Performance Appraisal is the systematic evaluation of the performance of employees and to understand the abilities of a person for further growth and development. The main Objectives of Performance Appraisal is to maintain records in order to determine compensation packages, wage structure, salaries raises, etc. and to identify the strengths and weaknesses of employees to place right person on right job. It is said that performance appraisal is an investment for the company that can be justified by following advantages: Promotion, Compensation, Employees Development, Selection Validation, Communication and Motivation. In this research paper we tried to identify the techniques of Performance Appraisal followed in aviation